Variation of Contact Angles in Brine/CO2/Mica System considering Short-Term Geological CO2 Sequestration Condition. (22nd April 2018) - Jafari, Mohammad; Jung, Jongwon
Abstract : Geological CO2 sequestration has been proposed as an effective solution to mitigate excessive human-emitted CO2 in atmosphere. Knowledge of immiscible two-phase flow of CO2 -water/brine is necessary to evaluate the efficiency and safety of geological storage sites. Among forces dominating fluid flow, capillary pressure is highly important because of high uncertainty in measurement due to ambiguous wettability behavior of geomaterials. In particular, time-dependent wettability of geomaterials is of interest for predicting short-term performance of the storage site. After injection of CO2 into an aquifer, both the CO2 and water/brine in rocks pores are unsaturated and tend to dissolve into each other. Present study investigates the variation of contact angle on mica sheet using a captive bubble method at a wide range of pressures and salinities under unsaturated condition. Our results showed a general increase of contact angle with time. Comparison of unsaturated contact angle with previous results in the literature showed a wide span of wettability behavior, ranging from receding to advancing contact angle values reported in the literature. The observed decrease in wettability by time due to heterogeneity and pinning effect of triple line can jeopardize the safety of geological carbon sequestration projects in short-term after injection of CO2 .